Evaluasi terhadap Waktu Tunggu dan Jarak Berjalan Penumpang pada Perpindahan Moda di Stasiun Lempuyangan Yogyakarta - Yuwono Wiarco; Siti Malkhamah (Faculty of Engineering, Universitas Gadjah Mada, 2005)
Lempuyangan Railway Station is located in Jogjakarta. To get to or to leave the station passengers using the railway services take other modes, such as becak, buses, taxis, and motorcycles (ojek). The process of mode changing is very importanl. To do so, passengers have to walk to the next mode stop and sometimes they have to wait for the vehicle arrival. Research was undertaken to investigate the performance of the mode changing process, in terms of waiting time and walking distance, based on site measurement and on what passengers perceived, to model the relationship between the performance expected and what perceived by the passengers, and to evaluate the performance using standards set by Directorate General of Land Transport. It was found that based on both direct measurement and passengers perception, the performance of the changing process was good. There was a very good relationship between what expected and what perceived by passengers. The waiting time and walking distance met the standards required.Kata kunci: perpindahan moda, waktu tunggu, jarak berjalan kaki.